HUBUNGAN KONTROL DIRI DENGAN PORKRASTINASI AKADEMIK PADA MAHASISWA STIKES YATSI TANGERANG - Putri Amanda Anwar; Ayu Pratiwi; Rina Puspitasari (Nusantara Hasana Berdikari, 2022)
Individuals often feel difficult and feel unable because of cases found in students. The case is not far from academic assignments. Individuals often ask for help from relatives or friends to do it, moreover some people have seen the results of the work done with their friends. So this causes students' skills to fall into the low category in self-control because they often ask individuals to complete the task. So that researchers need to research the relationship between self-control and academic procrastination. Research method descriptive correlation is used to determine the relationship between self-control variables and academic procrastination in STIKes Yatsi Tangerang students. The population is 184 STIKes Yatsi Tangerang students and a sample of 126 respondents is obtained. The sampling technique used was random sampling. The data taken in this study using google form. The chi-square test, the second sig value of the data is smaller than 0.005, so there is a relationship between self-control and academic procrastination.